Temperature and moisture effects on the failure of fibre metal laminates - Lim, Yi Ren (2019)
This project investigates the effects of moisture and temperature on the failure of different grades of GLARE. Three different grades of GLARE (grade 2, 3 and 4), with two variations of glass-fibre lay-up (type ‘A’ and ‘B’ lay-up) were used for the experiment. Half of the specimens were hygrothermal conditioned by placing it in a chamber at 80°C and 90% relative humidity. The specimens were put through tensile and three-point bending test. Properties such as Young’s Modulus, Ultimate Tensile Strength, Flexural strength, etc. were compared between specimens that were hygrothermal conditioned and lab conditioned. The results from this experiment shows that GLARE 2A possess the strongest tensile properties and second strongest bending properties. The effect of hygrothermal conditions did not significantly affect the results of the tensile and bending test.